Konservasi Rehabilitasi Sumberdaya Pesisir dan Laut untuk Penanaman Mangrove di Tanjung Tiram Desa Poka Ambon - Soukotta, Imanuel V.T; Manuputty, Gratia Dolores; Maureen, Tuapattinaja A.; Moniharapon, Domey Lowits; Saleky, D.V; Latue, Milyan Uli; Tino, Wildan; Barcinta, Muhammad Fahrul (Pakis Journal Institute, 2025)
The importance of mangrove forests in protecting coastlines from abrasion and erosion. The coastal mangrove area is experiencing serious problems in terms of mangrove area pollution, resulting in the death of mangrove seedlings, reducing density and abundance. Mangrove planting is often faced with several problems, such as lack of public awareness about the importance of mangrove ecosystems, environmental damage due to human activities, and lack of resources for planting and maintenance. Protection of mangrove areas is often faced with several problems, such as environmental damage due to human activities like illegal logging, pollution, and uncontrolled infrastructure development. In addition, lack of public awareness about the importance of mangrove ecosystems and lack of law enforcement also become obstacles in protecting mangrove areas. However, solutions to these problems can be done by increasing public awareness through education and campaigns, conducting mangrove planting in a structured and sustainable manner, and involving local communities in the planting and maintenance process. Thus, mangrove planting can be more effective and sustainable in maintaining the balance of coastal ecosystems and improving community welfare. This mangrove planting activity involves students and lecturers who participate actively and runs smoothly. It is expected that this activity will foster a sense of care among students in preserving and conserving mangrove areas in the future.